Відновлення сприятливого гідрологічного стану р. Чаплинка Дніпропетровської області. Сталий розвиток: захист навколишнього середовища - Коломойцева, К. К.; Чушкіна, І. В.; Максимова, Н. М. (Національний університет «Львівська політехніка», 2022)
The ecological condition of rivers in Ukraine is critical. All rivers have a high anthropogenic load, pollution, their natural balance is disturbed, they have lost the ability to self-clean. Water management development programs of Ukraine. According to the Law of Ukraine "On Approval of the National Target Program for Water Management and Ecological Rehabilitation of the Dnieper River Basin until 2021" the priority measures are to restore and maintain a favorable hydrological regime and ecological status of small rivers. On the example of the Chaplynka River, in order to improve the ecological and sanitary condition, it is planned to carry out hydraulic measures to widen the riverbed by clearing the riverbed of silt and changing stiffness as a result of clearing the riverbed of wetlands and aquatic vegetation.